Requesting Help Module Interface Design on Key Partial Video with Action and Augmented Reality for Children with Autism Spectrum Disorder - Chuan-Po Wang; Cheng-Hui Tsai; Yann-Long Lee (Applied Sciences, 2022)
Children with autism spectrum disorder (ASD) have marked difficulty with vocabulary, lack of language, or shortcomings with their ability to organize their oral expression; thus, they cannot effectively communicate with others. In particular, people with moderate or severe disabilities cannot systematically narrate an incident and cannot follow pragmatic rules provided by others. Their attempts at standard everyday conversation lead to cognitive problems. When children with ASD are faced with difficult circumstances, they are usually unable to seek help from others, which in turn can result in their being unable to communicate effectively. This research focused on three child participants with ASD and language disorders. The goal was to strengthen the effectiveness of their requesting help and to organize their oral expression, to use requesting help modules, to remove static key images, and to use augmented reality (AR) combined with the dynamic video clips in key partial video with action (KPV). This study developed request-assistance training in conjunction with an auto organizational menu (AOM), multiple case studies and withdrawal designs, training-response methods, and a comparison of outcomes. The proposed AR sentence intervention effectively increased the children’s desire to communicate with others and the accuracy rate of their help requests, and increased their level of communication. We conclude that the interface of our requesting help modules is efficacious enough to assist children with ASD at different levels. The proposed AR sentence intervention helps them build scenarios by themselves, helps them organize communication with their peers, and assists them to request help.